Elimination of misconduct in manual counting process as an improvement of inventory accuracy in a manufacturing company - Iman Haddad Qaisara Dhia, Mohd Mahzan; Lee, Khai Loon (Penerbit Universiti Malaysia Pahang, 2021)
Managing inventory is crucial especially for manufacturing companies as it has a direct influence on profits of the company. In order to have an efficient inventory management, inventory accuracy need to be achieved and this can be achieved by leveraging technologies and techniques that can minimize the human error. The objective of this study is to investigate the factors affecting inventory inaccuracy in Factory 21 of ABC manufacturing company. This study reveals that the inventory inaccuracy is influenced by the order received in the factory, which is due to the human misconduct during the manual counting process of cartons on pallet. This paper proposes the deployment of Arduino sensor network system in automating the carton counting process.The findings for this study show that the automation system able to improve the inventory record accuracy in ABC manufacturing company.